PENGELOLAAN DANA DESA DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DI DESA FATUKOTO KECAMATAN MOLLO UTARA KABUPATEN TIMOR TENGAH SELATAN PROVINSI NUSA TENGGARA TIMUR ( MANAGEMENT OF VILLAGE FUNDS IN INCREASING SOCIETY WELFARE IN FATUKOTO VILLAGE, NORTH MO - Andreas Letik (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2019)
ABSTRACT The purpose of this research is to know and analyze supporting and obstacle factors management of village funds in Fatukoto Village, North Mollo Subdistrict South Middle Timor District Province East Nusa Tenggara. The research is qualitative research with a descriptive approach. Techniques of data collection in this research are interview, observation, documentation and triangulation. The result of this study to show the management of village funds has not been efective and many physical development activities that causes the proverty rate has not descreased or preprosperous in Fatukoto Village. Empowerment programs and activities are implemented but not on target and there are no result to improve the welfare of society. Therefore, in this thesis the writer give an explanation of supporting and obstacle factors in management of village funds and the efforts to overcome obstacle factors such as increasing the quality, capacity, human resource competence, increasing socialization in other to encourage society participant, the using of village financial system (SESKEUDES) development capacity of village-owned business entity (BUMDES) ans also a change of the recruitment village technical personil system and finally can creating the quality and capacity of village funds management. Key words : Management, Village Funds, Welfare of Society